Transforming Accounting Theory through the Application of Artificial Intelligence (AI), Machine Learning (ML), and the Internet of Things (IoT): Approaches to Business Model Innovation, Risk Management, and Financial Prediction - Pratiwi Sidauruk; Grace Fiftyrina Sibarani; Iskandar Muda (Indo Publishing, 2025)
The integration of Artificial Intelligence (AI), Machine Learning (ML), and the Internet of Things (IoT) into accounting practices is revolutionizing traditional frameworks, offering new opportunities for business model innovation, enhanced risk management, and improved financial prediction. This paper explores the intersection of these emerging technologies with accounting theory, examining their transformative impact on financial reporting, auditing, and decision-making processes. AI and ML algorithms enable more accurate forecasting, anomaly detection, and automated decision-making, while IoT technologies facilitate real-time data collection and analysis, creating new avenues for operational efficiency and predictive capabilities. Despite these advancements, challenges such as the